Integral group ring of Rudvalis simple group - Bovdi, V. A.; Konovalov, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
Using the Luthar–Passi method, we investigate the classical Zassenhaus conjecture for the normalized unit group of the integral group ring of the Rudvalis sporadic simple group Ru . As a consequence, for this group we confirm the Kimmerle conjecture on prime graphs.